Pengaruh Strategi Promosi dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Tempat Makan Jepang di Majalaya - Hasna Najwa Sabrina; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the influence of promotional strategies and service quality on customer satisfaction at Ramen AA Majalaya Branch. Increasingly tight competition in the culinary sector requires business actors to implement effective promotional strategies and provide optimal service quality to create customer satisfaction. This study uses a quantitative method with a survey approach. The sample of this study was 74 respondents selected by accidental sampling technique. Data were collected using a questionnaire with a Likert scale of 1-5 which has been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with the help of SPSS software version 26. The results of the study show that promotional strategies have a positive and significant effect on customer satisfaction. Service quality also has a positive and significant effect on customer satisfaction. Simultaneously, promotional strategies and service quality have a significant effect on customer satisfaction. Service quality has a more dominant influence than promotional strategies. It can be concluded that effective promotional strategies supported by good service quality are very important to increase customer satisfaction at Ramen AA Majalaya. This research suggests integrating promotional strategies with service quality to create strong synergies for stakeholders.